Character Education in Developing the Careers of Children Special Needs in Vocational Providers School Inclusive - Mega Iswari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
This research aims to study and compile data is comprehensive, ranging from the new data and actual integrated on character education in developing the careers of children in need of special vocational education, then perform verification and validation data to identify where children in need of special vocational schools are there in having a good character in the development of his career as the blind children, deaf children and autistic children. They are capable of learning to follow suit with his talent and his interest in achieving careers in the future. Character education has always been integrated in every learning process in school either in a honesty, working, responsibility, confidence, persevering, meticulous and others. External research during the first year are learning implementation plan and the integrated learning materials on character education for individual learning in vocational secondary schools as education providers Inclusion in The City Of Padang.